Game Asset Design As A Culture Conservation Effort Through New Media - Rezaldi, Muhammad Yudhi; Alhafizi, Imam (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2023)
Indonesia has a very rich culture, but not much is known by the wider National community, even though some are known but are slowly being forgotten because they have been defeated by technological developments. The purpose of this research is to conserve culture in Toba Batak through new media packaged in digital game technology. Through this method, it is hoped that it can indirectly introduce regional culture to its target audience, namely youth people from the millennial generation. The methods Narrative Literature Review (NLR) that used are collecting data, analyzing data, determining assets, illustrating assets (sketching, coloring), assisting with asset illustrations, revising, and finalizing 2D asset designs. This design asset is succeeded creating 6 (six) game assets design in the form of 2D illustrations of the Batak Toba culture. That is, legendary figures, traditional clothing (men and women), traditional houses, traditional weapons, traditional food, and landscapes. In the future, this asset design will be made into a 3D model to be implemented into the game engine.